Epstein-Barr Virus (EBV) DNA as a potential marker of in vivo immunity in professional footballers - Perkins, E.; Davison, G. (Research Quarterly for Exercise and Sport, 2022)
Introduction: Team sport athletes have increased susceptibility to upper respiratory symptoms (URS) during periods of intensified training and competition. Reactivation of Epstein-Barr Virus (EBV) may be a novel marker for risk of upper respiratory illness (URI) in professional athletes.